City government in Hellenistic and Roman Asia minor - Dmitriev, Sviatoslav (OUP E-Books., 2005)
City Government in Hellenistic and Roman Asia Minor examines the social and administrative transformation of Greek society within the early Roman empire, assessing the extent to which the numerous changes in eastern Greek culture during the imperial period ought to be attributed to Roman influence.